2008
DOI: 10.1002/ijc.23773
|View full text |Cite|
|
Sign up to set email alerts
|

Glycodelin reduces breast cancer xenograft growth in vivo

Abstract: Malignant growth is characterized by loss of cell differentiation, uncontrolled proliferation and resistance to apoptosis. Many tumor suppressor genes that protect cells against malignant transformation regulate cell differentiation. Here, we show for the first time that glycodelin, a differentiation-related protein, reduces breast cancer tumor growth in vivo. We found that glycodelin cDNA-transfected MCF-7 breast cancer cells showed a differentiated phenotype and produced smaller tumors in mouse mammary fat p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 33 publications
(84 reference statements)
1
31
0
Order By: Relevance
“…Interestingly, the 30 most differentially regulated genes (Supplementary Tables 1 and 2) included several genes related to breast cancer metastasis and malignancy (Goodison et al, 2005;Minn et al, 2005;Buess et al, 2007;Gupta et al, 2007b;Hautala et al, 2008). The genes upregulated in GATA3-overexpressing cells included inhibitors of breast cancer growth and metastasis, such as PAEP (progestagenassociated endometrial protein) (Glycodelin) and DLC1 (deleted in liver cancer 1), whereas the prometastatic genes, ID1, ID3, LY6E, KRTHB1 and RARRES3, as well as the interferon-response genes, MX1, OAS1, G1P3 and IFI44L, were found to be downregulated in the presence of high GATA3 expression.…”
Section: Gata3 Regulates Metastasis-associated Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the 30 most differentially regulated genes (Supplementary Tables 1 and 2) included several genes related to breast cancer metastasis and malignancy (Goodison et al, 2005;Minn et al, 2005;Buess et al, 2007;Gupta et al, 2007b;Hautala et al, 2008). The genes upregulated in GATA3-overexpressing cells included inhibitors of breast cancer growth and metastasis, such as PAEP (progestagenassociated endometrial protein) (Glycodelin) and DLC1 (deleted in liver cancer 1), whereas the prometastatic genes, ID1, ID3, LY6E, KRTHB1 and RARRES3, as well as the interferon-response genes, MX1, OAS1, G1P3 and IFI44L, were found to be downregulated in the presence of high GATA3 expression.…”
Section: Gata3 Regulates Metastasis-associated Genesmentioning
confidence: 99%
“…Particularly, ID1 and ID3, were shown to facilitate secondary outgrowth of breast tumors metastases in the lungs (Gupta et al, 2007b), which is in agreement with the role of GATA3 identified here. Of note, DLC1, which inhibits lung metastasis of breast cancer cells (Goodison et al, 2005) and PAEP (glycodelin), which inhibits breast cancer growth (Hautala et al, 2008), were among the genes upregulated by GATA3. Hence, the combined repression of ID1/3, LY6E, KRTHB1 and RARRES3 and induction of DLC1 and PAEP in response to GATA3 overexpression may play a significant role in preventing lung metastasis.…”
Section: Gata3 In Breast Tumor Metastasis To the Lungmentioning
confidence: 99%
“…In hormone-responsive tumours, glycodelin-induced differentiation is related to the decreased expression of oncogenes and an increased expression of tumour suppressor genes, emphasising the tumour suppressor nature of glycodelin (Table 4). The role of glycodelin glycosylation in the transfected tumour cells is still an unresolved issue that may account for the diverse responses in the cell lines studied (104). But interestingly, glycodelin-inducing SAHA has been reported to act as a trans-differentitation agent in MCF-7 breast cancer cells (105).…”
Section: Breast Cancermentioning
confidence: 99%
“…Several studies have shown that glycodelin is not only associated with differentiated epithelium, but it also induces cell differentiation in endometrial and breast cancer cells [5][6][7][8][9][10][11]. Glycodelin differentiates MCF-7 breast cancer cells towards normal, less malignant direction [6,7].…”
Section: Introductionmentioning
confidence: 99%